PENATAAN ULANG RUANGAN DAN KOLEKSI BUKU PERPUSTAKAAN DALAM UPAYA PENINGKATAN MINAT BACA DAN KUNJUNGAN SISWA DI PERPUSTAKAAN UPT SMA NEGERI 7 BANYUASIN PADA MASA COVID-19 - Sajidah, Ana; Kurnia Vlora, Rani; Rohmaniyah, Rohmaniyah (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
The COVID-19 pandemic has had a significant impact on various sectors, including education. During that time, it has been observed that the reading interest in Indonesia, especially among school students, has decreased significantly due to the shift to remote learning The condition of the library also greatly affects its visitors. The spatial arrangement and collection at the UPT SMAN 7 Banyuasin Library are still disorganized and not fully optimized for its primary function as a school library. Therefore, the research aims to understand the rearrangement of space and collection of library materials in relation to increasing students' reading interest and visits to the library. The study is a descriptive qualitative research with data collection through observation, interviews, and direct documentation. The results of the study show that after the rearrangement of the space and library collection at the Banyuasin Library, which previously had few visitors, many students and teachers now visit the library, using it as a place for learning and as a center for literacy activities and creating reading boards.